Tensile Modeling Of Composite Epoxy Modified With Nanosilica Particles - ., Mulyadi; Siregar, A M (Fakultas Teknik UMSU, 2025)
The addition of nanosilica particles can enhance mechanical properties of epoxy based composite materials. Tensile behavior is very crucial properties to be investigated due to its appearance frequently in the application. The amount of nanosilica (SiO2) particles was added in 2%, 5%,8 % and 10% of weight to epoxy resin Epikote 828. Dogbone tensile specimens of epoxy modified with nanosilica were tested using universal tensile machine. The results of tensile properties were further elaborated using available analytical model and finite element analysis. Analytical model and finite element analysis using computer can cut the time to market. As the result, the cost can be minimized compare to experiment based assessment. Tensile behavior improvement is revealed as the nanosilica particles added. A very good correlation among the results from experiment, analytical and finite element analysis has been revealed.